Spirit Christology: rethinking Christo-centric theology - Welker, Michael (Leaning into the spirit, 2019)
The theology of the Reformation was thoroughly concentrated upon the revelation of God in Jesus Christ. It was correlated with an academic and educational revolution which particularly turned against speculative thought. Luther’s famous Heidelberg Disputation with its strong emphasis on what is called a “low Christology” and on a “theology of the cross” deeply impressed many young reformers. Many of Luther’s old friends and teachers, however, had serious questions and doubts about his rejection of the old metaphysical theology in favor of a low Christology. Similar questions come up today. “Only the suffering God can help!” said Dietrich Bonhoeffer in his letters from prison. Jürgen Moltmann published a famous book entitled “The Crucified God.” But how can a suffering and crucified God be of any help in a world full of violence, injustice, agony and distress?